2021
DOI: 10.1016/j.radcr.2021.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Repeated TACE in HCC after Fontan surgery and situs viscerum inversus: A case report

Abstract: We describe the case of a 32-year-old man who developed a liver neoplasm due to previous Fontan surgery (FS) for a single ventricle anomaly and situs viscerum inversus. He was admitted to our hospital for suspected hepatocellular carcinoma during an Ultrasound (US) follow up. Computed tomography (CT) showed features of chronic liver disease and 7 cm hepatic nodule with arterial enhancement. Laboratory analyses documented preserved liver function and increased levels of alpha-fetoprotein. Trans-arterial-chemoem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…[63][64][65][66][67] Gasparrini et al reported a patient with situs inversus totalis who underwent repeated TACE treatments after Fontan surgery. 68 Variant origin of the hepatic artery (from the superior mesenteric artery) further complicated the case.…”
Section: Interventional Radiology (Ir)mentioning
confidence: 97%
“…[63][64][65][66][67] Gasparrini et al reported a patient with situs inversus totalis who underwent repeated TACE treatments after Fontan surgery. 68 Variant origin of the hepatic artery (from the superior mesenteric artery) further complicated the case.…”
Section: Interventional Radiology (Ir)mentioning
confidence: 97%